IMPLEMENTASI AFFIRMATIVE ACTION KUOTA PEREMPUAN DALAM PARTAI POLITIK DAN LEMBAGA PERWAKILAN RAKYAT DAERAH (Studi di Wilayah Kota Malang) - Sirajuddin Sirajuddin; Adiloka Sudjono (Widya Yuridika, 2018)
In the 2009 legislative general election, there were 793 definitive candidates, consisting of 528 men and 265 women. Therefore, the average percentage of definitive female candidates from the whole parties was 33% and in general it seems that the percentage was above 30%. But, an affirmative action as stated on the law on the election of the house of representative members in Malang city in 2009 was not reached, since the number of the elected female legislative representative was still under quota of 30%. Factors causing such less optimum affirmative action in political parties and the house of representative in Malang city are as follows: (1) the political context dominated by men so that the women’s interest was less accommodated. (2) the social context dominated by men so this resulted in masculine practices and (3) the cultural context dominated by a patriarchal tradition resulting a social construction on the division of men and women, and the legal factor through the decision of the constitutional court that did not condition the legislative candidates based on the highest voters, instead of the number order.  Kata Kunci: affirmative action, perempuan, partai politik, lembaga perwakilan rakyat daerah